Experience of short-term continuous glucose monitoring in people with Type 1 diabetes with persistent poor glycemic control. (September 2015) - A Adamson, Karen; Hassanein, Mohamed; Malik, Iqbal; Vora, Jiten
SUMMARY : Aim: This study assessed the effect of short/intermittent use of continuous glucose monitoring in poorly controlled Type 1 diabetes.Methods: A 6-month, multicenter, single-arm, pilot study, enrolling 32 people on multiple daily injections who had completed a structured education program. The primary end point was to evaluate HbA1c change from baseline to 6 months.Results : Median HbA1c change from baseline was -0.4% at day 21, -0.3% at day 95 and -0.3% at 6 months. At 6 months, 44% of participants had a ≥0.5% HbA1c reduction from baseline. Hypoglycemia frequency and time spent in hypoglycemia did not change.Conclusion: Short/intermittent use of continuous glucose monitoring with real-time glucose values, in conjunction with a healthcare professional diabetes management review, resulted in significant HbA1c improvements.